Confirmation bias a ubiquitous phenomenon in many guises - Nickerson, Raymond S. (©1998., 1998)
Confirmation bias, as the term typically used in the psychological literature, connotes the seeking or interpreting of evidence in ways that are partial to existing beliefs, expectations, or a hypothesis in hand. The author reviews evidence of such a bias in a variety of guises and gives examples of its operation in several practical contexts. Possible explanations are considered, and the question of its utility or disutility is discussed.
Includes bibliographical references.
Keywords: Discrimination -- Religious aspect; Prejudices